The breathable city an advocacy campaign on urban sustainability through the promotion of urban green spaces in Quezon City, Philippines - Muit, Ilsa Maria Andrea R.
Quezon City, being the largest city in Metro Manila Philippines, is not far from urbanization, industrialization and urban decay. There will be unplanned urban sprawl and rise of land share. People choose to shift to urban living for many reasons such as economic success, family, education and livelihood opportunities. But with these comes an underlying counterpart of disadvantages to the city, such as increase in pollution, poverty and losses of natural resources. In return, this may lead to the failure in functionality as a city. With these in mind, United Nations refined the Sustainable Development Goals 2030 Agenda. Under "Goal 11", out of 17 planned goals, this goal focuses on sustainable cities and communities. This mainly secures the decency of urban life quality of citizens that includes prosperity without harming the environment. To ensure cities to be safe, inclusive, healthy, functioning and productive is one of the greatest challenges humankind is facing right now. Although, a lot of people fail to consider what lies within the urban premises that will help them find the answer in making their cities successful and sustainable -- and these are the urban green spaces. Fortunately, Quezon City has the largest amount of urban green spaces in the Metro but it is still questionable if these places are being prioritized by the city government, developers and dwellers. This study aims to promote these urban green spaces in Quezon City through a campaign which advocates urban green spaces' importance in initiating a healthy and sustainable city to live in.